Pengaruh Afek pada Persepsi Risiko dan Sikap Konsumen dalam Pembelian Produk Negara Asing - , Dian Eka Mayasari, Dr. B.M. Purwanto. M.B.A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This paper examines the effect of positive affect and negative affect toward social risk, psychological risk and consumer attitude in foreign product purchase decision.The 127 undergraduate student involve as participant for this experimental factorial design 3(positive affect/negative affect/neutral) x 2(utilitarian/symbolic). Negative affect is stimulated by mentioning name of animosity country and positive affect is stimulated by mentioning name of affinity country. The data was analyzed using MANOVA. The study result shows that affect influencing attitude, psychological risk and social risk. Positive and negative affect influencing dependent variable in different way. Participant perceive social risk and psychological risk toward product from animosity country is higher that product from affinity country. This study result also reveals that the influence of affect toward attitude, social risk and psychological risk would be higher for the symbolic product rather than utilitarian. Again, it shows that negative affect and positive affect are different construct in a different continuum. Keyword: Affect, social risk, psychological risk, attitude, animosity, affinity